DARI KERAMAIAN KE KONVERSI: TINJAUAN LITERATUR SISTEMATIS BERBASIS PRISMA ATAS FENOMENA ROJALI–ROHANA DAN TANTANGAN KEBERLANJUTAN KEWIRAUSAHAAN RITEL DI INDONESIA - Ika Suhartanti Darmo; Muhammad Oceano Fauzan (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study examines how the Indonesian phenomenon of Rojali (crowds who rarely buy) and Rohana (crowds who only ask) can be repositioned as a retail entrepreneurship and sustainability issue rather than merely a social-media label. Using a PRISMA-guided systematic literature review, the paper synthesizes 20 core studies published between 2015 and 2025 on showrooming, webrooming, channel switching, and omnichannel retailing, identified through scholarly searches across major publisher databases and academic search engines. A statistical meta-analysis was not performed because the reviewed studies were highly heterogeneous in constructs, contexts, and outcome measures; therefore, a qualitative-thematic synthesis was employed. The review reveals four major insights. First, low-conversion traffic is driven by economic uncertainty, value consciousness, risk-reduction motives, need for touch, digital search convenience, and social-experiential motivations. Second, Rojali-Rohana behavior is conceptually closer to showrooming, webrooming, and broader cross-channel switching than to pure non-consumption. Third, the phenomenon creates a dual effect for retailers: lower in-store conversion and margin pressure on the one hand, but richer behavioral data and new conversion opportunities on the other. Fourth, sustainable retail entrepreneurship requires a shift from transaction-centric selling to integrated omnichannel conversion systems combining trust signaling, assisted selling, experiential retail, and customer data activation. The novelty of this paper lies in bridging an indigenous Indonesian market phenomenon with the global literature on omnichannel consumer behavior and proposing an integrative framework for conversion-oriented and sustainability-sensitive retail entrepreneurship